The constant term of a binomial expansion of nth order `(x+a)^n` is iven by `a^n` .
Therefore the constant term `= 2^9`
Therefore the constant term of `(x+2)^9` is 512.
The binomial expansion states `(a+b)^n=sum_(k=0)^n(nCk)a^(n-k)b^k`
In our case `(x+2)^9=sum_(k=0)^9(9Ck)x^(9-k)2^k`
The only term without x will be when k=9 => x^0=1. Hence that term will be equal to `9C9*1*2^9=1*1*512=512`
So the only constant is 512
The expansion would look like:
x^9 + ....... + 2^9
We only care about the last term:
2^9 = 512